Reduced suppressive effect of beta(2)-adrenoceptor agonist on fibrocyte function in severe asthma - Lo,C-Y; Michaeloudes,C; Bhavsar,PK; Huang,C-D; Chang,P-J; Wang,C-H; Kuo,H-P; Chung,KF (RESPIRATORY RESEARCH, 2017)
BackgroundPatients with severe asthma have increased airway remodelling and elevated numbers of circulating fibrocytes with enhanced myofibroblastic differentiation capacity, despite being treated with high doses of corticosteroids, and long acting β2-adrenergic receptor (AR) agonists (LABAs). We determined the effect of β2-AR agonists, alone or in combination with corticosteroids, on fibrocyte function.MethodsNon-adherent non-T cells from peripheral blood mononuclear cells isolated from healthy subjects and patients with non-severe or severe asthma were treated with the β2-AR agonist, salmeterol, in the presence or absence of the corticosteroid dexamethasone. The number of fibrocytes (collagen I+/CD45+ cells) and differentiating fibrocytes (α-smooth muscle actin+ cells), and the expression of CC chemokine receptor 7 and of β2-AR were determined using flow cytometry. The role of cyclic adenosine monophosphate (cAMP) was elucidated using the cAMP analogue 8-bromoadenosine 3′,5′-cyclic monophosphate (8-Br-cAMP) and the phosphodiesterase type IV (PDE4) inhibitor, rolipram.ResultsSalmeterol reduced the proliferation, myofibroblastic differentiation and CCR7 expression of fibrocytes from healthy subjects and non-severe asthma patients. Fibrocytes from severe asthma patients had a lower baseline surface β2-AR expression and were relatively insensitive to salmeterol but not to 8-Br-cAMP or rolipram. Dexamethasone increased β2-AR expression and enhanced the inhibitory effect of salmeterol on severe asthma fibrocyte differentiation.ConclusionsFibrocytes from patients with severe asthma are relatively insensitive to the inhibitory effects of salmeterol, an effect which is reversed by combination with corticosteroids.